Cranial Focal Nodular Haematopoietic Hyperplasia: A case report and literature review. (July 2018) - Yakoub, Kamal Makram; Zisakis, Athanasios; Ughratdar, Ismail
Highlights: Focal Nodular Haematopoietic Hyperplasia. First case report of this pathology in the skull. Differential diagnosis and management of cranial Focal Nodular Haematopoietic Hyperplasia. Literature review of the previously report cases. Abstract: Focal Nodular Haematopoietic Hyperplasia (FNHH) is an uncommon, benign, osteolytic lesion and so far, has not been reported cranially. Here, we report the first cranial case of a patient with right frontal bone FNHH and describe the clinical history, management and follow up with review of the literature of this rare pathology.